Effects of hall current on the hydromagnetic free convection with mass transfer in a rotating fluid - Agrawal H.L.; Ram P.C.; Singh V. (My University, 2025)
An exact analysis of Hall current on hydromagnetic free convection with mass transfer in a conducting liquid past an infinite vertical porous plate in a rotating fluid has been presented. Exact solution for the velocity field has been obtained and the effects of m (Hall parameter), E (Ekman number), and Sc (Schmidt number) on the velocity field have been discussed. © 1984 D. Reidel Publishing Company.